Deregulated Issues In Electricity Market - Ramani, Anis Niza; Hassan, Mohd Yusri; Abdullah, Md Pauzi; Hussin, Faridah; Jasmani, Noor Zarith Iffah (Penerbit UTM, 2008)
This book is written primarily as an introduction to power systems electricity market. It is intended for students in electrical and other engineering disciplines that have interest in deregulated electricity market and issues related to it. The first chapter in this book discusses the basic two electricity market models; Single Buyer Market Model and Pool Market Model. Chapter 2 deals with the issue of congestion cost allocation method for pool market structure. Chapter 3 describes certain aspects to be considered in pricing the unbundled transmission services. Chapter 4 for discusses the issue of transmission losses allocation in electricity market. Chapter 5 discusses on the transmission congestion management assessment. Finally Chapter 6 discusses security cost allocation through game theory.